2001
DOI: 10.1207/s1532690xci1903_1
|View full text |Cite
|
Sign up to set email alerts
|

Spurious Correlations in Mathematical Thinking

Abstract: How does detection of correlational structure affect mathematical thinking and learning? When does correlational information lead to erroneous problem solving? Are experienced students susceptible to misleading correlations? This work attempts to answer these questions by examining a source of systematic errors termed the spurious-correlation effect. This effect is hypothesized to occur when a student perceives a correlation between an irrelevant feature in a problem and the algorithm used for solving that pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 28 publications
3
20
0
Order By: Relevance
“…While answering the items in the physics test, students likely tried to "imagine" more or less the situation described in these items, rather than treating these items as meaningless "word problems" that, consequently, would elicit a stereotyped or standard mathematical model (see also Van Dooren et al 2007, 2008. Studies in mathematics education have shown that students often perceive mathematical word problem solving at school as a puzzle-like activity with little or no relation to the real world (see Verschaffel et al 2000), which can often be successfully accomplished by relying on superficial cues that help students to decide which operations to perform (Ben-Zeev and Star 2001;Hinsley et al 1977;Schoenfeld 1988). Additional evidence for students' less superficial approach in physics problem solving lies in the fact that students in this study were also influenced by other domain-specific misconceptions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…While answering the items in the physics test, students likely tried to "imagine" more or less the situation described in these items, rather than treating these items as meaningless "word problems" that, consequently, would elicit a stereotyped or standard mathematical model (see also Van Dooren et al 2007, 2008. Studies in mathematics education have shown that students often perceive mathematical word problem solving at school as a puzzle-like activity with little or no relation to the real world (see Verschaffel et al 2000), which can often be successfully accomplished by relying on superficial cues that help students to decide which operations to perform (Ben-Zeev and Star 2001;Hinsley et al 1977;Schoenfeld 1988). Additional evidence for students' less superficial approach in physics problem solving lies in the fact that students in this study were also influenced by other domain-specific misconceptions.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The use of keyword methods, focusing on surface level features, does not emphasize the meaning and structure of the problem and thus may not help students to reason and make sense of story situations to be able to successfully solve novel problems (e.g., Ben-Zeev & Star, 2001;Van de Walle, 2007). Our approach moves away from keywords and superficial problem features and more explicitly focuses on helping students see the underlying mathematical structure of problems.…”
mentioning
confidence: 99%
“…As a result of applying the key word method, students struggling in mathematics have persistent difficulties in mathematical problem solving despite plenty of practice. The keyword method does not emphasize the meaning and structure of the problem and thus may not help students to reason and make sense of problem situations, which is crucial in solving novel problems (Ben-Zeev & Star, 2001). …”
Section: Mathematical Problem Solving and Traditional Instructionmentioning
confidence: 99%